Tea consumption and bone health in Chinese adults: a population-based study - Li, X; Qiao, Y; Yu, C; Guo, Y; Bian, Z; Yang, L; Chen, Y; Yan, S; Xie, X; Huang, D; Chen, J; Chen, Z; et al. (Springer Nature, 2018)
Summary Tea is a worldwide drink with controversial effect on bone health. The sex-specific associations are unrevealed among general population. This study showed that prolonged moderate tea consumption benefited bone health in women, while no additional benefit with stronger tea. However, tea consumption was not associated with bone health in men. Introduction Tea consumption has been shown a potentially beneficial effect on bone health in postmenopausal women. However, little is known about such association in men, and whether stronger tea instead harms bone health due to elevated urinary excretion of calcium associated with caffeine in the tea. The aim of this study was to examine the association between various metrics of tea consumption and bone health. Methods The present study included 20,643 participants from the China Kadoorie Biobank (CKB), who have finished both baseline survey (2004–2008) and a re-survey (2013–2014). They were aged 38–86 years at re-survey. Tea consumption was self-reported at both baseline and re-survey. Bone mineral density (BMD) was measured using calcaneal quantitative ultrasound once at re-survey. Results Compared with non-consumers, prolonged weekly tea consumers in women was associated with higher calcaneus BMD measures, with β (95% CI) of 0.98 (0.22, 1.74) for BUA, 4.68 (1.74, 7.61) for SOS, and 1.95 (0.81, 3.10) for SI. Among prolonged weekly tea consumers, no linear increase in BMD measures with the amount of tea leaves added was observed. The SOS and SI were higher in consumers with tea leaves 3.0–5.9 g/day than in those with < 3.0 g/day, but were reduced to non-significant for those with ≥ 6.0 g/day. Tea consumption was not associated with calcaneus BMD measures in men. Conclusion Prolonged moderate tea consumption benefited bone health in women but not in men. For stronger tea consumption with more tea leaves added, neither benefit nor harm to bone health was observed.